Pattern of internet use and its association with academic performance among undergraduate medical students of Silchar Medical College, Assam - Deka, Nirman; Dey, Ajit K. (International Journal Of Community Medicine And Public Health, 2025)
Background: The internet has emerged as an essential tool in medical education, providing widespread access to academic resources. While it offers numerous benefits, excessive or unregulated use may adversely affect students’ academic performance. This study aimed to assess the patterns of internet usage, levels of internet addiction, and their association with academic performance among undergraduate medical students at Silchar Medical College, Assam. Methods: A descriptive cross-sectional study was conducted among MBBS students across all academic years. Data were collected using a pre-designed, pretested, self-administered questionnaire comprising socio-demographic details, internet usage behavior, and the internet addiction test (IAT). Academic performance was measured using internal assessment and university examination scores. Statistical analysis included chi-square tests and logistic regression to determine associations between variables. Results: A total of 188 students participated in the study. The majority (56.4%) demonstrated mild internet addiction, 20.2% moderate, and 23.4% normal usage. A statistically significant association was observed between daily internet usage and year of study (p=0.005), with senior students spending more time online. Demographic factors such as gender, place of residence, and guardian’s occupation were significantly associated with internet addiction levels. Conclusion: Internet use among medical students is widespread and generally perceived as academically beneficial. However, the presence of mild to moderate levels of addiction in a substantial proportion of students calls for timely interventions. Promoting balanced internet use and digital literacy could help optimize academic outcomes and safeguard students' well-being.